2008
DOI: 10.1007/s10103-008-0541-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-level (gallium-aluminum-arsenide) laser irradiation of Par-C10 cells and acinar cells of rat parotid gland

Abstract: We investigated cell response, including cell proliferation and expression of heat stress protein to clarify the influence of low-level (Ga-Al-As diode) laser irradiation on rat parotid gland acinar cell-derived Par-C10 cells. Furthermore, we also investigated amylase release and cell death to irradiation in rat parotid gland acinar cells. Number of Par-C10 cells in the laser-irradiated groups was higher than that in the non-irradiated group at days 5 and 7, although the difference was statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
6
1
4
Order By: Relevance
“…26,31 As a result of mitochondria stimulation, increase in adenosine triphosphate (ATP) levels, increase in glucose consumption by the cells, and the intracellular calcium level, LLLT can promote cell proliferation and increase in the antiapoptotic protein expression, as well as increase blood microcirculation in the salivary glands. 19,29,32,33 However, the present study has not confirmed the hypothesis that LLLT could stimulate residual gland function in patients who have had head and neck radiotherapy. No significant difference was observed between laser and control groups regarding the SFR and OHIP-14 scores and VAS.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…26,31 As a result of mitochondria stimulation, increase in adenosine triphosphate (ATP) levels, increase in glucose consumption by the cells, and the intracellular calcium level, LLLT can promote cell proliferation and increase in the antiapoptotic protein expression, as well as increase blood microcirculation in the salivary glands. 19,29,32,33 However, the present study has not confirmed the hypothesis that LLLT could stimulate residual gland function in patients who have had head and neck radiotherapy. No significant difference was observed between laser and control groups regarding the SFR and OHIP-14 scores and VAS.…”
Section: Discussioncontrasting
confidence: 77%
“…All the selected patients presented important salivary dysfunction as a consequence of radiotherapy. Although the literature show, in pre-clinical and clinical studies, the benefits of LLLT in salivary flow increase, 16,19,20,[26][27][28][29][30] there is not any study investigating its effects on patients who have already undergone radiotherapy treatment, and present hyposalivation and xerostomia as sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Dokazano je da primena laseroterapije utiče i na ubrzanje mitoze epitelnih ćelija izvodnih kanala pljuvačnih žlezda, jer se pospešuje njihova regeneracija [26,27]. Takođe, ima potvrda da laseroterapija utiče na stimulaciju dotoka pljuvačke [28], promenu enzimske aktivnosti pljuvačke i njenog sastava očitovanog u sniženju nivoa peroksidaze i katalaze, te povećanoj količini ukupnih proteina u pljuvački nakon laseroterapije [28][29][30][31][32].…”
Section: Laser Therapy Increases Par-clo Cell Pr O L Iferation and Exunclassified
“…Dosad je ovaj terapijski postupak opisan kao superiorniji od drugih, konvencionalnih vidova terapije, te se s velikom uspešnošću primenjuje u raznim granama medicine i stomatologije [33]. Između ostalog, laseroterapija se pokazala uspešnom i kao terapijska metoda za zbrinjavanje simptoma kserostomije [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Poseban akcent stavljen je na uspešniji ishod terapijskog zbrinjavanja kserostomije posle više uzastopno ponovljenih tretmana laseroterapijom nego u pojedinačnom tretmanu [20,23,24].…”
Section: Diskusijaunclassified
“…Low-level laser irradiation (LLLI) has a variety of biological effects, such as increasing cell proliferation and differentiation [10][11][12], inhibiting cell apoptosis [13], modulating immune responses [14], promoting wound healing [15], and decreasing the pathogenicity of fungal infections [16]. Aged RPE cells partly lose their proliferative ability and many physiological functions that are modulated by RPE functional proteins.…”
Section: Introductionmentioning
confidence: 99%